2022
DOI: 10.1155/2022/3437364
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence-Based Deep Learning Model for the Performance Enhancement of Photovoltaic Panels in Solar Energy Systems

Abstract: This study looks into artificial intelligence methods for scaling solar power systems, such as standalone, grid-connected, and hybrid systems, in order to lessen environmental effect. When all essential information is provided, conventional sizing methods may be a feasible alternative. It is impossible to apply typical procedures in instances where data is unavailable. The new suggested artificial intelligence model employing multilayered perceptrons is employed for sizing solar systems, and this model functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Available groundwater and solar energy access in sensitive watersheds may jeopardize water security through excessive abstraction. Solar power generation is inherently unreliable due to its reliance on weather deviations; to estimate how well solar power generation can generate energy at a specific location at a particular moment, weather predictions must be prepared in advance [34]. One of the limitations of the research is that solar cells have a lower power conversion efficiency (PCE) than conventional PV cells.…”
Section: Challenges and Future Scopementioning
confidence: 99%
“…Available groundwater and solar energy access in sensitive watersheds may jeopardize water security through excessive abstraction. Solar power generation is inherently unreliable due to its reliance on weather deviations; to estimate how well solar power generation can generate energy at a specific location at a particular moment, weather predictions must be prepared in advance [34]. One of the limitations of the research is that solar cells have a lower power conversion efficiency (PCE) than conventional PV cells.…”
Section: Challenges and Future Scopementioning
confidence: 99%
“…Their findings demonstrated that optimizing artificial intelligence could improve solar tracking systems. In a related study, Meena et al (2022) utilized AI algorithms to improve the performance and reduce the cost of photovoltaic (PV) systems, indicating that AI‐based solutions may be able to reduce the environmental impact of PV power systems.…”
Section: Applications Of Artificial Intelligence In Solar and Wind En...mentioning
confidence: 99%
“…This confirms the efficacy and viability of employing a "Convolutional neural network model" like "SolarNet" for forecasting solar radiation and emphasizes the possibility for new research areas in forecasting. Meena et al, 2022 investigate how "Solar power systems," particularly "Standalone, grid-connected," and hybrid systems, can be scaled using artificial intelligence (AI) techniques to lessen their environmental impact. The paper presents a hybrid AI sizing model built on multilayered perceptrons that combines the advantages of both AI and traditional sizing techniques.…”
Section: Studies Using Ai For Enhancement Of Pv In Solar Energy Systemsmentioning
confidence: 99%